2021
DOI: 10.1590/1980-549720210008.supl.2
|View full text |Cite
|
Sign up to set email alerts
|

Leisure time physical activity among Brazilian adults: National Health Survey 2013 and 2019

Abstract: Objective: The aim of this study was to analyze the prevalence of leisure-time physical activity in 2013 and 2019 according to sociodemographic characteristics in Brazilian adults. Methods: We analyzed data from the National Health Surveys conducted in 2013 and 2019. Prevalence of leisure-time physical activity (150+ minutes per week in physical activities) was calculated according to gender, age, education, race/skin color, Federative Units, and regions of Brazil in 2013 and 2019. Poisson regression models a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 25 publications
(32 reference statements)
4
15
1
5
Order By: Relevance
“…The recommended level of physical activity is higher among men, while women spend more time watching TV. This pattern varies a lot according to the indicators analyzed 37 , although the behavior is commonly described in the literature 37,38,39 . Historically women have different roles than men in our society.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The recommended level of physical activity is higher among men, while women spend more time watching TV. This pattern varies a lot according to the indicators analyzed 37 , although the behavior is commonly described in the literature 37,38,39 . Historically women have different roles than men in our society.…”
Section: Discussionmentioning
confidence: 93%
“…Intrinsic sexist structures in society can explain this pattern39. More studies are need to seeking solutions for this behavior and to promote equity 39 .…”
Section: Discussionmentioning
confidence: 99%
“…As observed herein, in a study conducted with 3323 Iranian adults during the pandemic, the result suggested a significant association between improved sleep quality and well‐being among those who practiced physical activity (Akbari et al, 2021). Before the pandemic, it was estimated that 31.1% of the global population did not meet the physical activity recommendations (Hallal et al, 2012) In Brazil, only 30.1% were active during leisure time (Mielke et al, 2021) in 2019. While during the period of social isolation, Da Silva et al (2021) showed that physical inactivity increased 26% in the national territory (Da Silva et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The strengths of this study include the objective measurement of PA using techniques and approaches that are rare in countries like Brasil, unlike most of the previous studies that used questionnaires for indirect measurement of PA 4 . As far as we know, this is the first study that investigated the associations between accelerometry data with NC in Brasil.…”
Section: Discussionmentioning
confidence: 99%
“…Gerson Luis de Moraes Ferrari 1, 2 Eduardo Rossato de Victo 2 Irina Kovalskys 3 Aline Veroneze de Mello 4 Agatha Nogueira Previdelli 5 Dirceu Solé 2 Mauro Fisberg 6…”
Section: Sedentary Behavior Physical Activity and Body Composition In...unclassified